Guia de ações de controle da tuberculose na atenção primária à saúde de um município do Médio Mearim - Maranhão - Santos, Michael Jakson Silva dos (Universidade do Vale do Rio dos Sinos, 2024)
Tuberculosis is a global health problem that inspires searches for effective control strategies, given the devastating power it has on society. It is estimated that more than 10 million people fall ill each year, with more than one million deaths worldwide, being the main cause of death among people with HIV. Objective: to develop an action guide for tuberculosis control, for a municipality in the middle Mearim region, aimed at Primary Health Care professionals. Method: a methodological study was carried out in four stages: 1st) documentary study; 2nd) quantitative study – epidemiological data; 3rd) descriptive study – description of the health network, and 4th) preparation of a guide for action guidelines for tuberculosis control, for a municipality in the middle Mearim region, aimed at Primary Health Care professionals. Documentary research was carried out in the five Brazilian regions, North, Northeast, Central-West, South and Southeast, identifying the two capitals in each region of the country with the highest incidence of tuberculosis, using keywords in the search on the websites of the capitals, in order to find guides, manuals and documents related to tuberculosis. The descriptive study was to characterize the local health network. In the quantitative research, indicators related to tuberculosis in the municipality under study were collected. Results: of the ten capitals researched, documents of interest to the research were found on four websites, São Paulo-SP, Rio de Janeiro-RJ, Florianópolis-SC and Porto Alegre-RS. The websites of the Ministry of Health, Notifiable Diseases Information System – Tuberculosis (SINAN/TB), Mortality Information System (SIM), allowed an epidemiological survey of tuberculosis indicators until the year 2022. The Municipal Health Plan, of the municipality under study provided a description of the health network, these results supported the preparation of the Guide. Discussion: the analysis of the capitals' websites revealed that, although visually attractive, many of them do not provide efficient navigation and availability of necessary information. In the epidemiological indicators, it was found that, although the incidence of the disease in the municipality under study is almost double that of the national and state levels, the operational indicators for treatment, cure, directly observed treatment, abandonment, contacts examined, present satisfactory results, very close than recommended. The coverage of the Primary Care Network in the municipality under study reaches close to 95%. It was also found that 96.6% of tuberculosis control actions in Brazil are carried out by nurses. Final considerations: the present study had important implications related to health policies, where evidence was identified that the analysis of indicators, knowledge of the Health Care Network and the existence of documents, collaborate with the preparation of guides, and that nursing has a role essential in the control of tuberculosis. The limitations of the research, including the scarcity of documents on the websites of the capitals researched and outdated information, required additional searches to be carried out on other websites and platforms. However, this limitation did not prevent the execution of the central objective of this work, the development of the product, the guide for tuberculosis control actions in primary health care in Bacabal, which subsidizes tuberculosis control actions, when stated objectively. and aligned with the reality of local Primary Health Care.
Keywords: Guia; Manual; Controle; Tuberculose; Guide; Control; Tuberculosis; ACCNPQ::Ciências da Saúde::Enfermagem